Heuristic cues as perceptual filters : factors influencing public support for nuclear research reactor in Singapore - Ho, Shirley S. (2021)
Nuclear energy is an important consideration for decarbonisation. However, for Singapore – a country at the nascent stage of nuclear energy development – the building of a nuclear research reactor could be a precursor to a full-fledged nuclear energy plan. Guided by the cognitive miser model and the knowledge deficit model, this study examines factors shaping public support for the use of a nuclear research reactor for medical purposes. In particular, we seek to understand how different types of knowledge could affect public support for the use of a nuclear research reactor in an island city-state. Based on the data from a nationally representative door-to-door survey of 1000 adult Singaporeans, we found that the public mainly depend on heuristics, such as religiosity, benefit perception, and trust in relevant authorities, to form attitudes towards the use of a nuclear research reactor, revealing a tendency to employ mental shortcuts for decision making. More importantly, we found that heuristics moderated the effect of contextual nuclear knowledge on public support for the use of a nuclear research reactor. This indicates that individuals might interpret the same information differently, depending on their firmly held beliefs or pre-existing perceptions.